THE INFLUENCE OF LEARNING MOTIVATION AND EDUCATION COST THAT IS NEED IN UNIVERSITY TOWARD LEARNING ACHIVEMENT COLLEGE STUDENTS OF ECONOMIC EDUCATION PROGRAM STKIP PGRI WEST SUMATERA - Weni, Mestika - (Pendidikan Ekonomi, 2014)
This research intent to analyze : 1) the influence of learning motivation toward learning achievement college students of economic education concentrate of accountancy STKIP PGRI West Sumatera 2) the influence of education cost toward learning achievement college student of economic education concentrate to accountancy STKIP PGRI West Sumatera 3) the enfluence of learning motivation and education cost as together toward learning achievement college students of economic education concentrate to accountancy STKIP PGRI West Sumatera.The time of this research is doing on September 2014, the kind of the research that is used in this research is descriptive assosiatif research. The population of this research are all of college student economic concentrate of accountancy grade of 2011 and 2012, amount of 233 cillege students. The technique of taking sampel with proposional rundom sampling that the sampel amount of 70 college students. The technique of the data analysis : descriptif analysisand inductive analysis, is maximum experiment likelohood, ramsey experiment, normality experiment, heteroskedasticity experiment, multicoloniarity experiment, auto corelasion experiment and biviliar regresy analysis by the helped of spss program versi 16.The result of this research show that : 1) containt of the influence that positive and significant between lerning motivation toward lerning achievement college students of economic education bused on the result of data analysis that providible the value t hitung > ttabel (5,544 > 1, 29376), containt of the influence that positive and significant between education cost towards learning achievement college students of economic education based on the result of data analysis that prividible the value t hitung > t tabel (8,868 > 1,29376), containt of the influence that positive and significant as together between learning achievement college students of economic education concentrate of accountancy STKIP PGRI West Sumatera based on the result of data analysis F hitung > F tabel (288,474 > 2,74) and R square 0,896.Based on the result of the research have to suggest to the college students parents to pay attention and quide lerning activity students at home so that they can manage the time to learn. And donât forget to give then attention toward the cost that is need of the student in education in order to teach the maximum gold.